Cattle manure characteristics in relation to manure accumulation period and seasonal impacts in the intermountain west - Bhowmik, Priya R., author; Sharvelle, Sybil, advisor; De Long, Susan, committee member; Olsen, Daniel, committee member (Colorado State University. Libraries, 2023)
Anaerobic digestion (AD) of organic waste has been studied and implemented in practice more recently than ever. AD is used to produce biogas, which mainly consists of methane gas that has multiple purposes. Arguably the most important purpose methane gas has is that it is a renewable energy source. Organic waste that can serve as feedstock for AD ranges from food waste to animal waste, including manure. There are limited application of AD technology to process beef cattle manure compared to other manure sources due to factors such as method of collection processes (i.e., scraped on dry lots) and inconsistent methane gas produced due to varied conditions. This study focuses on beef cattle manure from the intermountain west, home to many cattle feedlots producing millions of tons of manure a year. Beef cattle feedlots pens typically have a base of compacted manure with no roof covering the pen. With no roof over the beef cattle feedlots and low collection frequency, the manure is exposed to seasonal change with varying weather conditions and often contains low water content and high inorganic material compared to other animal feeding operation manure. To improve the methane production of beef cattle manure in AD processes, more information is needed on the quality of beef cattle manure over varying collection frequency and seasons. The objective of this research is to determine biochemical methane potential (BMP) for differing accumulation time periods and seasonal impact. Four sample collections were conducted at one concentrated animal feeding operation (CAFO) from different months with different seasonal effects. For each sample collection, different manure accumulation periods were selected ranging from 7 to 90-day old manure. For each accumulation period, three cattle pens were selected based on the similar number of cattle and same feed. All manure was collected from each pen and was weighed with subsequent testing for characteristics. Based on the total solids (TS) from each pen in each manure accumulation period the composite sample was created for the manure accumulation period which was tested for BMP. A second manure collection technique was used due to complications with collecting lower manure accumulation periods with the first collection technique such as an uneven surface of the pen. The second technique applied land surveying one singular pen for a 10- and 20-day manure accumulation period to attempt to only collect newly deposited manure over the accumulation period. The BMP data is expressed as the volume of methane (CH4) produced per unit of volatile solids (VS) added, typically represented as mL CH4/ g VS feedstock. VS is the portion of the material that is organic and for this study in terms of volatile mass per dry mass. The sample collections from this study BMP results ranged from 200-276 mL CH4/ g VS feedstock. A literature review was conducted comparing over 13 studies that tested beef manure in AD. Results from this study were above the average of the literature review which was 160 mL CH4/ g VS feedstock. One of the sample collections occurred in May, which was the only data which represented a parallel trend between manure accumulation periods and BMP results, with BMP decreasing with longer accumulation periods. The May sample collection produced the highest measured ultimate BMP and was considered the most precise manure collection. Statically different trends were not observed for samples collected over seasons, leading to inconclusive results on seasonal impacts on BMP. The land surveying technique for manure collection resulted in variable quality manure, which emphasized the struggle of replication of manure collected and the possibility of obtaining only the desired manure accumulation period without obtaining any of the manure pad. Overall, results indicated the potential for increased methane production potential for more frequently collected manure at beef feedlots. However, the study also indicated that more frequent collection of only freshly deposited manure would be difficult to implement in practice.
Keywords: beef cattle manure; anaerobic digestion; biochemical methane potential